The chromatin remodeling factor OsINO80 promotes H3K27me3 and H3K9me2 deposition and maintains TE silencing in rice - Kangxi Du; Jiabing Wu; Jiachen Wang; Wenhao Xie; Liufan Yin; Xiang Li; Chao Li; Aiwu Dong (Nature Communications)
Abstract The INO80 chromatin remodeling complex plays a critical role in shaping the dynamic chromatin environment. The diverse functions of the evolutionarily conserved INO80 complex have been widely reported. However, the role of INO80 in modulating the histone variant H2A.Z is controversial. Moreover, whether INO80 helps regulate heterochromatin remains unknown. Here, we characterize the regulatory effects of OsINO80 on protein-coding genes and transposable elements (TEs) in rice. Upon OsINO80 overexpression in rice, we found three types of OsINO80-occupied regions with different chromatin signatures: type I (enriched with H2A.Z), type II (enriched with H3K9me2), and type III (deficient in H2A.Z/H3K9me2). Loss of OsINO80 results in a decrease in H3K27me3, but not H2A.Z, at type I regions as well as a decrease in H3K9me2 at type II regions, which correlates with TE activation and transposition. Our findings reveal that OsINO80 facilitates H3K27me3 establishment, promotes H3K9me2 deposition, and maintains TE silencing.